Evolution of and horizontal gene transfer in the Endornavirus genus. - Dami Song (Public Library of Science (PLoS), 2013)
The transfer of genetic information between unrelated species is referred to as horizontal gene transfer. Previous studies have demonstrated that both retroviral and non-retroviral sequences have been integrated into eukaryotic genomes. Recently, we identified many non-retroviral sequences in plant genomes. In this study, we investigated the evolutionary origin and gene transfer of domains present in endornaviruses which are double-stranded RNA viruses. Using the available sequences for endornaviruses, we found that Bell pepper endornavirus-like sequences homologous to the glycosyltransferase 28 domain are present in plants, fungi, and bacteria. The phylogenetic analysis revealed the glycosyltransferase 28 domain of Bell pepper endornavirus may have originated from bacteria. In addition, two domains of Oryza sativa endornavirus, a glycosyltransferase sugar-binding domain and a capsular polysaccharide synthesis protein, also exhibited high similarity to those of bacteria. We found evidence that at least four independent horizontal gene transfer events for the glycosyltransferase 28 domain have occurred among plants, fungi, and bacteria. The glycosyltransferase sugar-binding domains of two proteobacteria may have been horizontally transferred to the genome of Thalassiosira pseudonana. Our study is the first to show that three glycome-related viral genes in the genus Endornavirus have been acquired from marine bacteria by horizontal gene transfer.